Morphological characterization of mutant lines of Nagina22 in rice (Oryza sativa L.) - N. P. Sakthi Avinash; K. Manonmani; R. Muthuvijayaragavan; S. Rajeswari; S. Manonmani; M. Raveendran and; P. Jeyaprakash (Electronic Journal of Plant Breeding, 2019)
Rice plays a major role in feeding more than half of the world`s population with total production of about 769.9 million tonnes all over the world. India is an inland to vast varieties of rice cultivars, landraces and many lesser known varieties that have been cultivated by farmers as well as local promoters. These cultivars were refined through selection depend on enticing characters such as grain yield, grain length, cooking quality, aroma and refitting to various abiotic stresses. Collection, preservation and characterization of such cultivars may provide great opportunity to utilize them in crop improvement. A set of 542 Nagina 22 mutants were morphologically characterized under DUS test guidelines and compared with Nagina 22 as a check variety. Characterization has confirmed the existence of Distinctness, Uniqueness and Stability for the traits studied as given in the guidelines. Based on this research highly distinguish rice genotypes would be opt for forwarding this to further generation and registration as farmers variety. And these genotypes can also be used in crop improvement event in terms of both quality traits and high yield even as source or breeding material for pest and disease resistance.